Adaptasi Guru Pendidikan Pancasila dan Kewarganegaraan terhadap Kurikulum Merdeka di SMP Negeri 12 Kota Gorontalo - Pohontu, Veti; Adhani, Yuli; Yunus, Rasid (STAI Auliaurrasyidin Tembilahan, 2024)
This study aims to evaluate the readiness of Pancasila and Civic Education (PPKn) teachers in facing changes towards the Merdeka Belajar Curriculum which marks a significant transition from the previous K13 Curriculum. Qualitative methods were used in this study by applying observation, interview, and documentation techniques. Data analysis includes data reduction, narrative presentation, and conclusion drawing. The research findings show that teachers have a good understanding and are able to implement the Merdeka Curriculum in accordance with the provisions set by the government, including in integrating the three themes of the Pancasila Student Project: Democratic life, sustainable lifestyle, and local wisdom. However, the obstacles faced include the lack of facilities and infrastructure at SMP Negeri 12 Gorontalo City, especially related to the construction of a new building which affects the availability of the field.